1995
DOI: 10.1002/jmr.300080126
|View full text |Cite
|
Sign up to set email alerts
|

Study of cell‐free protein synthesis in aqueous two‐phase systems

Abstract: Protein synthesis in an aqueous two-phase system is reported here as a novel type of extractive bioconversion. Translation of BMV RNA was studied using either rabbit reticulocyte lysate or wheat-germ extract in aqueous dextran-PEG systems. Both polymers inhibited protein synthesis and the translation system partitioned into both phases. In the rabbit reticulocyte two-phase system, protein synthesis reached 30% of that in free solution, while in wheat-germ extract it was 60% of that in free solution. Protein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…9,10 Others demonstrated that transcription–translation (T/T) can be carried out in vesicles 11 and in bulk aqueous two-phase systems (ATPS). 12,13 By combining these approaches, it should be possible to produce genetically encoded proteins that distribute between coexisting phases as a model for cellular microcompartments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Others demonstrated that transcription–translation (T/T) can be carried out in vesicles 11 and in bulk aqueous two-phase systems (ATPS). 12,13 By combining these approaches, it should be possible to produce genetically encoded proteins that distribute between coexisting phases as a model for cellular microcompartments.…”
Section: Introductionmentioning
confidence: 99%
“…One approach toward gaining insight into the organizational features of cellular life is to construct mimetic systems in the laboratory that display similar organization and behavior. , Several recent studies have defined a set of chemical conditions that give rise to two coexisting aqueous phases in lipid vesicles. , Others demonstrated that transcription–translation (T/T) can be carried out in vesicles and in bulk aqueous two-phase systems (ATPS). , By combining these approaches, it should be possible to produce genetically encoded proteins that distribute between coexisting phases as a model for cellular microcompartments.…”
Section: Introductionmentioning
confidence: 99%
“…Moving on from transcription, translation has also been studied within phase-separated compartments. Cell-free mRNA translation processes in PEG/dextran ATPS can occur unimpeded, and are of interest to large scale production of proteins in bioindustrial applications (Marszal et al 1995). Targeted mRNA suppression and translation has also been observed to occur within a membraneless organelle inside eukaryotic cells (Reinkemeier et al 2019).…”
Section: Biological Processes Imbued Into Llps Systemsmentioning
confidence: 99%
“…Compartments can even be made without a membrane at all [20]. Neither aqueous two-phase systems [21,22], polyelectrolyte polymer containing coacervates [23], hydrogels [24], microfluidic chip-based compartments [25,26], nor bead-based systems [27] contain a membrane.…”
Section: Chemical Communication Between Artificial Cellsmentioning
confidence: 99%